2021
DOI: 10.3389/fcell.2021.653798
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Analysis Reveals a Potential Regulatory Mechanism of LncRNA-FNIP2/miR-24-3p/FNIP2 Axis in Chicken Adipogenesis

Abstract: Lipid biosynthesis is a complex process, which is regulated by multiple factors including lncRNA. However, the role of lncRNA in chicken abdominal fat accumulation is still unclear. In this research, we collected liver tissues from six high abdominal fat rate Sanhuang broilers and six low abdominal fat rate Sanhuang broilers to perform lncRNA sequencing and small RNA sequencing. A total of 2,265 lncRNAs, 245 miRNAs, and 5,315 mRNAs were differently expressed. Among of them, 1,136 differently expressed genes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…These studies provided new insights into the molecular mechanisms to explore fat metabolism in pigs. Also, the study found there was a lncRNA-FNIP2/miR-24-3p/FNIP2 axis, which can regulate lipid metabolism in Sanghuang chicken liver ( Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies provided new insights into the molecular mechanisms to explore fat metabolism in pigs. Also, the study found there was a lncRNA-FNIP2/miR-24-3p/FNIP2 axis, which can regulate lipid metabolism in Sanghuang chicken liver ( Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immortalized chicken preadipocyte cell line (ICP1) was obtained from the Key Laboratory of Chicken Genetics and Breeding, Ministry of Agriculture and Rural Affairs, Northeast Agricultural University (Harbin, China). The ICP1 cell line was established by infecting chicken stromal-vascular cells with a recombinant retrovirus expressing chicken telomerase RNA [11] ; these cells share common morphology and differentiation features with primary preadipocytes and are widely used in chicken adipogenesis studies [ 14 16 ] . ICP1 and DF-1 cell lines (ATCC, Manassas, USA) were cultured in DMEM F-12 (Gibco, Carlsbad, USA) and DMEM high glucose (Gibco) respectively, supplemented with 10% fetal bovine serum (Gibco) and maintained at 37°C in a 5% CO 2 cell incubator [ 11 , 17 ] .…”
Section: Methodsmentioning
confidence: 99%
“…The immortalized chicken preadipocyte ICP1 [24] and chicken fibroblast DF-1 [25] cell lines were kindly provided by the Key Laboratory of Chicken Genetics and Breeding, Ministry of Agriculture and Rural Affairs, Northeast Agricultural University (Harbin, China). ICP1 cells have been widely used to study chicken adipogenesis [26, 27], as they present the same morphological and differentiation characteristics as primary preadipocytes [24, 26, 27]. DF-1, an immortalized chicken fibroblast cell line, can be easily transiently transfected with exogenous DNA.…”
Section: Methodsmentioning
confidence: 99%